Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41380-022-01653-0
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-derived hiPSC brain microvascular endothelial-like cells show impairments in angiogenesis and blood–brain barrier function

Abstract: Schizophrenia (SZ) is a complex neuropsychiatric disorder, affecting 1% of the world population. Long-standing clinical observations and molecular data have pointed out a possible vascular deficiency that could be acting synergistically with neuronal dysfunction in SZ.As SZ is a neurodevelopmental disease, the use of human induced pluripotent stem cells (hiPSC) allows disease biology modeling retaining the patient's unique genetic signature. Previously, we reported a VEGF-A signaling impairment in SZ-hiPSC der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In this regard, one can see parallels between inflammatory processes in autism and another genetically related developmental disorder, schizophrenia (SCZ) [ 155 , 156 ] In SCZ, inflammatory markers are associated with cortical expansion and impaired blood brain barrier function which correlates with symptom severity [ 157 , 158 ]. Using human induced pluripotent stem cells, SCZ-derived brain endothelial cells have decreased vasculogenesis and permeability, and decreased ZO-1 expression (tight junction protein) with altered cellular localization in the cytoplasm [ 159 ]. These data suggest that both the expression of gene variants of signaling pathways (protein kinases C, G, and A, RhoA, PI3/Akt, and Wnt) which control BBB function in patients and investigation of the disrupted pathways in autism may yield druggable targets [ 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one can see parallels between inflammatory processes in autism and another genetically related developmental disorder, schizophrenia (SCZ) [ 155 , 156 ] In SCZ, inflammatory markers are associated with cortical expansion and impaired blood brain barrier function which correlates with symptom severity [ 157 , 158 ]. Using human induced pluripotent stem cells, SCZ-derived brain endothelial cells have decreased vasculogenesis and permeability, and decreased ZO-1 expression (tight junction protein) with altered cellular localization in the cytoplasm [ 159 ]. These data suggest that both the expression of gene variants of signaling pathways (protein kinases C, G, and A, RhoA, PI3/Akt, and Wnt) which control BBB function in patients and investigation of the disrupted pathways in autism may yield druggable targets [ 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these pathways, the NOTCH and WNT pathways are described as having variants in several of their pathway components, increasing the risk of developing the disease. In addition to their well-known role in neurodevelopment, these pathways are important regulators of angiogenesis, a process that is proposed to be downregulated in SZ patients ( Lopes et al, 2015 ; Katsel et al, 2017 ; Casas et al, 2018 ; Casas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This deficiency in VEGFA signaling has also been corroborated by in vitro SZ hiPSC modeling using NSC. Interestingly, brain microvascular EC derived from SZ-hiPSC have a decreased angiogenic response when stimulated with VEGFA ( Casas et al, 2018 ; Casas et al, 2022 ). However, VEGF protein levels in the superior temporal gyrus (STG) are not significantly different between SZ and control groups ( Izumi et al, 2021 ).…”
Section: Vascular Endothelial Growth Factor (Vegf) Signaling Is Highl...mentioning
confidence: 99%
“…Disruption of the BBB has been documented in schizophrenia, suggesting an association between BBB hyperpermeability and the pathogenesis of schizophrenia [ 63 , 64 , 65 , 66 , 67 ]. In an in vitro study using patient-derived ECs, human iPSCs consistently revealed an intrinsic failure in brain microvascular endothelial-like cells of patients with schizophrenia, thereby affecting proper angiogenesis and the BBB function, which may contribute to altered neurovascular crosstalk during schizophrenia [ 68 ]. Furthermore, epidemiological findings suggest that the risk of certain types of cancer, such as respiratory cancer, is significantly lower in patients with schizophrenia than in those without schizophrenia [ 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Neurodevelopmental and Neuropsychiatric Disorders Associated...mentioning
confidence: 99%